Training Materials on Climate-Smart Rice Production for Extension Staff and Rice Farmers in Vietnam - National Agriculture Extension Center, Vietnam (2019)
With support from the International Rice Research Institute (IRRI), the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA), and the Climate and Clean Air Coalition, the National Agriculture Extension Center of Vietnam developed a series of modules (guidelines and presentations) tackling topics such as: adaptive cropping calendar (rice varieties, soil preparation, and crop establishment); water management; pest management; waste and by-product management, reducing post-harvest losses; scaling and evaluation; climate change and greenhouse gas (GHG); and presentation skills.